2021
DOI: 10.3390/pr9040702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Binary Chemical Reaction and Activation Energy on Heat and Mass Transfer of Marangoni Driven Boundary Layer Flow of a Non-Newtonian Nanofluid

Abstract: The flow and heat transfer of non-Newtonian nanofluids has an extensive range of applications in oceanography, the cooling of metallic plates, melt-spinning, the movement of biological fluids, heat exchangers technology, coating and suspensions. In view of these applications, we studied the steady Marangoni driven boundary layer flow, heat and mass transfer characteristics of a nanofluid. A non-Newtonian second-grade liquid model is used to deliberate the effect of activation energy on the chemically reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…The RHS's last word reflects the extra consequence of the chemical reaction. Using Rosseland approximation of radiation, [45][46][47] the radiative heat flux is simplified as…”
Section: Heat and Mass Transfer Analysismentioning
confidence: 99%
“…The RHS's last word reflects the extra consequence of the chemical reaction. Using Rosseland approximation of radiation, [45][46][47] the radiative heat flux is simplified as…”
Section: Heat and Mass Transfer Analysismentioning
confidence: 99%
“…Casson liquid is classified as a shear depleting liquid with an indeterminable thickness at zero shear rate. Recently, Gowda et al [6] examined the heat and mass transfer of the Marangoni driven boundary layer flow of a non-Newtonian nanofluid by considering the effects of binary chemical reactions and activation energy. Dahab et al [7] investigated the MHD Casson nanofluid movement over a non-linearly warmed porous medium with suction/injection in the presence of an expanding surface effect.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Madhukesh et al [29] used non-Fourier heat flux model over curved stretching surface to investigate the impact of AA7072-AA7075/water-based hybrid nanofluid along with Newtonian heating when temperature at the wall is constant. In 2021, two dimensional laminar flow of non-Newtonian Marangoni nanofluids in presence of activation energy along with chemical reactions has been presented by Gowda et al [30] and they showed that heat transfer rate declines with larger Marangoni number. Very recently, Yusuf et al [31] studied the bio-convective entropy generation effect induced by inclined plate in presence of Williamson nanofluid.…”
Section: Introductionmentioning
confidence: 99%